Answer:
Option C is correct.
The value of g(-2) is smaller than the value of g(4)
Step-by-step explanation:
Given the function: [tex]g(x) = 8x -2[/tex] ......[1]
Compare and contrast g(-2) and g(4).
find g(-2);
substitute the value of x = -2 in [1] we get;
[tex]g(-2) = 8(-2) -2 = -16-2 =-18[/tex]
Similarly ,
For g(4);
Substitute the value of x = 4 in [1];
[tex]g(4) = 8(4) -2 = 32-2 =30[/tex]
Compare g(-2) and g(4);
g(-2) = -18
g(4) = 30
then; g(-2) < g(4)
As you can see the value of g(4) is larger than the value of g(-2) or in other words, we can say that the value of g(-2) is smaller than the value of g(4)